(untitled) (International Journal of Engineering and Computer Science, 2018)
The exploration of new materials with comparative performance at affordable costs facilitated the outcome of emerging innovative products of green composite materials. In the current work, natural oil palm frond fibres were used in long and random fiber form as reinforcement in polyester matrix to fabricate green composites using the hand layup technique. Some mechanical, physical and processing property tests were conducted to elucidate the utilization potentials of green composites of oil palm frond fibre in the building industry. In overall, the results showed that the tensile strength and impact strength properties decreased with the increase in fibre loading. The modulus of elasticity increased with the increase in fibre loading up to 60wt. % before dropping. The values of both the flexural strength properties and modulus of rigidity increased with the increase in fibre loading. Even though the fibres were used without surface treatment in this work, the result of respective values of 0.07, 4.27% and 2.08 for the mould linear shrinkage, porosity and specific gravity, including a low water absorption uptake of 6.98%, propounds an indication that green composites of oil palm frond could be acceptable in areas of low strength and moderate flexure applications in the building industry.